2018
DOI: 10.1002/itl2.70
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of different precoding matrices for PAPR reduction in OFDM systems

Abstract: Orthogonal frequency division multiplexing (OFDM) is an attractive technique for wireless communication systems due to its ability to mitigate frequency selectivity. However, OFDM suffers from high peak‐to‐average power ratio (PAPR) problem, which reduces the power amplifier (PA) efficiency or worse it degrades bit error rate (BER) performance and increases out‐of‐band radiation. In literature, there are different PAPR reduction techniques. Among them PAPR reduction by precoding matrices has small computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The authors in [ 11 , 10 ] showed that SRC precoding ( Section 3.1 ) and Log companding ( Section 3.2 ) are the best precoding and the best companding techniques from BER and OOB-radiation reduction points of view. Therefore, they are selected to be hybridized in the proposed technique, and their parameters are adjusted to increase the reduction of BER and OOB-radiation.…”
Section: Proposed Hybrid Precoding-companding Techniquementioning
confidence: 99%
See 4 more Smart Citations
“…The authors in [ 11 , 10 ] showed that SRC precoding ( Section 3.1 ) and Log companding ( Section 3.2 ) are the best precoding and the best companding techniques from BER and OOB-radiation reduction points of view. Therefore, they are selected to be hybridized in the proposed technique, and their parameters are adjusted to increase the reduction of BER and OOB-radiation.…”
Section: Proposed Hybrid Precoding-companding Techniquementioning
confidence: 99%
“…Fortunately, the SRC matrix does not increase the distortion. However, it causes some data rate loss [ 11 ]. Precoding matrix R is given as: …”
Section: Proposed Hybrid Precoding-companding Techniquementioning
confidence: 99%
See 3 more Smart Citations